Why Fresh Milk Matters. Issue 5 (September 2022) - Spatz, Diane L.
Abstract : Ideally, all babies feed directly at the breast and receive milk at the perfect temperature with no preparation required. This is not always reality for many families for a variety of reasons. Our breastfeeding expert, Dr. Spatz, discusses the importance of feeding fresh breastmilk to hospitalized babies as much as possible, with the next best alternative as the mother's previously frozen, thawed breastmilk.